2020
DOI: 10.1186/s12906-020-2866-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of gamma-aminobutyric acid-enriched fermented Hovenia dulcis extract on ethanol-induced liver injury in mice

Abstract: Background: Various extracts of Hovenia dulcis have been commonly used in Asia for cases of alcohol-related disorders. Fermentation is reported to enhance the level and biological activities of various bio-constituents of plant extracts. Therefore, this study was undertaken to evaluate the effects of fermented H. dulcis extract (FHDE) on ethanol-induced liver injury in mice. Methods: FHDE was prepared using Bacillus subtilis and Lactobacillus plantarum. The effects of FHDE on ethanolinduced liver injury were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…A wide range of traditional foods produced by microbial fermentation contain GABA, in which GABA is safe and eco-friendly, and also has the possibility of providing new health-benefited products enriched with GABA [ 21 ]. Numerous studies have demonstrated that GABA-enriched functional food have physiological benefits such as suppression of blood pressure [ 22 ], hepatoprotection [ 23 ], decrease in gut inflammation [ 24 ], and regulation of glucose tolerance [ 25 ]. Furthermore, several reports have demonstrated that GABA promoted bone health [ 15 , 16 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of traditional foods produced by microbial fermentation contain GABA, in which GABA is safe and eco-friendly, and also has the possibility of providing new health-benefited products enriched with GABA [ 21 ]. Numerous studies have demonstrated that GABA-enriched functional food have physiological benefits such as suppression of blood pressure [ 22 ], hepatoprotection [ 23 ], decrease in gut inflammation [ 24 ], and regulation of glucose tolerance [ 25 ]. Furthermore, several reports have demonstrated that GABA promoted bone health [ 15 , 16 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation results in increased antioxidant activity of an extract due to the increased number of phenolic compounds and flavonoids as a direct result of microbial hydrolysis [27]. GABA is widely used as a food supplement [2]. GABA was abundantly present in the FSC used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…HDE (Hovenia dulcis) was used as a positive hepatoprotective agent in alcohol-induced hepatotoxic rats. HDE is approved as a dietary supplement to prevent alcohol-induced liver damage by the Ministry of Food and Drug safety (MFDS) in Korea [2,24].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, fruits, peduncles, and seeds of H. dulcis are used for several diseases like febrifuge, antispasmodic, laxative, and hangover syndrome [6][7][8]. Recent studies have proved that extracts of H. dulcis have detoxification on alcohol poisoning [9][10][11], hepatoprotective [10,12], antioxidant [13,14], antidiabetic [15], antiobesity [16], antiallergic [17], and anticancer activities [18][19][20]. Because of these medicinal properties, there is a trial for functional foods and natural health products by using extracts of H. dulcis [21].…”
Section: Introductionmentioning
confidence: 99%